Application of Criminal Sanctions Against Illegal Mining Perpetrators According to Law Number 3 of 2020 - Laras Cipta Ilahi; Nirwan Junus; Jufryanto Puluhulawa (Estudiante Law Journal, 2023)
The purpose of this study is to determine and analyze the application of criminal sanctions against illegal mining actors according to Law Number 3 of 2020 in Dengilo District, Pohuwato Regency, and to determine and analyze the impact of illegal mining in Dengilo District, Pohuwato Regency. The type of research used in this study is empirical legal research using data collection techniques through direct observation and interviews with related parties. The results of this study show that the application of criminal sanctions in Kec. Dengilo is still not optimal, because there are still many perpetrators who continue to carry out activities secretly at the mine site. The miners carried out mining activities at night using heavy equipment even though it had been prohibited by the authorities. The government of Dengilo District, Pohuwato District, has made socialization efforts to the community regarding the provisions governing mining problems and sanctions for those who violate these provisions and has collaborated with the Pohuwato Regional Police in following up perpetrators of illegal gold mining crimes by the provisions of Law Number 3 of 2020. The impact caused by illegal gold mining in Dengilo District is positive: increasing local income, accommodating labor, and increasing community income. Negative impacts: river water pollution, damage to agricultural land, destruction of forest areas, causing casualties, causing landslides, and disrupting public health. Therefore, the government should facilitate and determine community mining areas.